Estimasi Potensi Produksi Ikan Di Danau Laut Tawar Berdasarkan Morphoedaphic Index - Saiful Adhar; Ternala Alexander Barus; Esther Sorta Mauli Nababan; Hesti Wahyuningsih; Erlangga Erlangga; Munawwar Khalil (Jurnal Serambi Engineering, 2020)
Laut Tawar Lake is located in Aceh Tengah District is the largest lake in Aceh Province. The lake, located at an altitude of 1230 meters above sea level, produces about 13 species of freshwater fish. Fish depik (Rasbora tawarensis), eyas (Rasbora sp.), and relo (Rasbora sp.) are endemic species of Laut Tawar Lake. This study aims to estimate the potential of fish production based on the value of morphoedaphic index. The observation was conducted for one year, from October 2016 until September 2017. The measurement of electric conductivity value of lake waters was conducted on 7 (seven) stations selected purposively in the lake area about 5870 hectares. The results showed that morphoedaphic index value of Laut Tawar Lake ranged from 5.10 to 7.84 with an average of 6.14. Potential of fish production in the lake is 33.47 kg/ha/yr with total potential of fish production of 196.49 ton/yr. The value shows a decrease of 10.93 kg/ha/yr over a period of 22 years. This decrease is caused by changes in morphometry parameters and water quality of Laut Tawar Lake.